Effects of statin therapy on coronary artery plaque volume and high-risk plaque morphology in HIV-infected patients with subclinical atherosclerosis: a randomised, double-blind, placebo-controlled trial. Issue 2 (February 2015) - Lo, Janet; Lu, Michael T; Ihenachor, Ezinne J; Wei, Jeffrey; Looby, Sara E; Fitch, Kathleen V; Oh, Jinhee; Zimmerman, Chloe O; Hwang, Janice; Abbara, Suhny; Plutzky, Jorge; Robbins, Gregory; et al.
Summary: Background: HIV-infected patients have a high risk of myocardial infarction. We aimed to assess the ability of statin treatment to reduce arterial inflammation and achieve regression of coronary atherosclerosis in this population. Methods: In a randomised, double-blind, placebo-controlled trial, 40 HIV-infected participants with subclinical coronary atherosclerosis, evidence of arterial inflammation in the aorta by fluorodeoxyglucose (FDG)-PET, and LDL-cholesterol concentration of less than 3·37 mmol/L (130 mg/dL) were randomly assigned (1:1) to 1 year of treatment with atorvastatin or placebo. Randomisation was by the Massachusetts General Hospital (MGH) Clinical Research Pharmacy with a permuted-block algorithm, stratified by sex with a fixed block size of four. Study codes were available only to the MGH Research Pharmacy and not to study investigators or participants. The prespecified primary endpoint was arterial inflammation as assessed by FDG-PET of the aorta. Additional prespecified endpoints were non-calcified and calcified plaque measures and high risk plaque features assessed with coronary CT angiography and biochemical measures. Analysis was done by intention to treat with all available data and without imputation for missing data. The trial is registered withClinicalTrials.gov, numberNCT00965185 . Findings: The study was done from Nov 13, 2009, to Jan 13, 2014. 19 patients were assigned to atorvastatin and 21 to placebo. 37 (93%) of 40 participants completed the study, with equivalent discontinuation rates in both groups. Baseline characteristics were similar between groups. After 12 months, change in FDG-PET uptake of the most diseased segment of the aorta was not different between atorvastatin and placebo, but technically adequate results comparing longitudinal changes in identical regions could be assessed in only 21 patients (atorvastatin Δ −0·03, 95% CI −0·17 to 0·12, vs placebo Δ −0·06, −0·25 to 0·13; p=0·77). Change in plaque could be assessed in all 37 people completing the study. Atorvastatin reduced non-calcified coronary plaque volume relative to placebo: median change −19·4% (IQR −39·2 to 9·3) versus 20·4% (−7·1 to 94·4; p=0·009, n=37). The number of high-risk plaques was significantly reduced in the atorvastatin group compared with the placebo group: change in number of low attenuation plaques −0·2 (95% CI −0·6 to 0·2) versus 0·4 (0·0, 0·7; p=0·03; n=37); and change in number of positively remodelled plaques −0·2 (−0·4 to 0·1) versus 0·4 (−0·1 to 0·8; p=0·04; n=37). Direct LDL-cholesterol (−1·00 mmol/L, 95% CI −1·38 to 0·61 vs 0·30 mmol/L, 0·04 to 0·55, p<0·0001) and lipoprotein-associated phospholipase A2 (−52·2 ng/mL, 95% CI −70·4 to −34·0, vs −13·3 ng/mL, −32·8 to 6·2; p=0·005; n=37) decreased significantly with atorvastatin relative to placebo. Statin therapy was well tolerated, with a low incidence of clinical adverse events. Interpretation: No significant effects of statin therapy on arterial inflammation of the aorta were seen as measured by FDG-PET. However, statin therapy reduced non-calcified plaque volume and high-risk coronary plaque features in HIV-infected patients. Further studies should assess whether reduction in high-risk coronary artery disease translates into effective prevention of cardiovascular events in this at-risk population. Funding: National Institutes of Health, Harvard Clinical and Translational Science Center, National Center for Research Resources.